THE EFFECT OF GOVERNMENT EXPENDITURE AND NUMBER OF POPULATION ON MAKASSAR CITY REGIONAL ORIGINAL INCOME - Asdar, Asdar; Naidah, Naidah (Perpustakaan dan Penerbitan Unismuh Makassar, 2020)
This study aims to determine the effect of government spending and population on local revenue in Makassar City. The analysis method used in this research is multiple linear regression. Based on the results of the calculation of SPSS version 2.3, it shows that government spending has a positive and significant effect on Regional Original Income (PAD) in Makassar City, where the regression coefficient is 1.108 with a significant level of 0.011 (0.011 <0.05). Meanwhile, the population has a negative and significant effect on Regional Original Income (PAD) in Makassar City, where the regression coefficient is -5.861 with a significant level of 0.003 (0.003 <0.05).